P174 Identifying non-adherence with asthma medication and the relationship to clinical outcomes amongst adults with difficult-to-control asthma. (16th November 2010) - Murphy, A C; Proeschel, A; Linnett, M E; Brightling, C E; Wardlaw, A J; Pavord, I D; Bradding, P; Green, R H
Abstract : Background: The failure of patients to adhere to prescribed medication regimens is well documented. The clinical effects of non-adherence can include treatment failure, unnecessary, potentially dangerous and costly intensification of therapy, complications and hospitalisations. The extent of non-adherence and the clinical implications in difficult-to-treat asthma were audited. Method: A total of 161 adult asthma patients attending a difficult asthma clinic during July/August 2009 were included in the audit. GPs retrospective prescription refill data for asthma medicines, patient demographics and clinical outcome data were collated. The medication adherence ratio was calculated as the number of doses refilled/number of doses prescribed ×100 for a mean duration of 12 months. Adherence was defined as adequate if the ratio was ≥80%. Results: Prescription refill data for 132 patients were available (82%), and 115 patients were included in the audit. Poor adherence was identified in 75/115 patients (65.2%) on inhaled corticosteroids (ICS) overall – 64/101 (63.4%) taking combined ICS and long acting β2 agonist (LABA) inhalers and 11/14 (78.6%) patients taking separate ICS and LABA inhalers (p=0.24). In the 14 patients using separate ICS and LABA, adherence to the LABA (50%) was significantly better than adherence to the ICS (14.3%) (p=0.043). Patients with poor adherence to ICS had a lower post-bronchodilator FEV1 (75.4 (20.9) vs 84.3 (23.5), p=0.049) and higher sputum eosinophil counts (4.6 (0.66)% vs 2.3 (0.54)%, p=0.05) than those with adequate ICS adherence. There were no significant differences in age, gender, racial origin, smoking history or courses of rescue oral prednisolone between these two groups. Patients with poor ICS adherence were more likely to have been ventilated for asthma (19.2% vs 2.6%, p=0.02). In a multivariate logistic regression model, the adherence ratio was the only independent predictor of previous need for ventilation for acute severe asthma (p=0.008). Thus for each 10% decrease in adherence to ICS, the estimated odds of having been ventilated for asthma increased by 1.85 times. Conclusion: The majority of patients with difficult-to-control asthma are non-adherent with their asthma medication. Patients using separate ICS and LABA inhalers use the LABA more than the ICS. Non-adherence is correlated with several poor clinical outcomes.